Chemical tools for studying phosphohistidine: generation of selective τ-phosphohistidine and π-phosphohistidine antibodies - Makwana, Mehul V.; dos Santos Souza, Cleide; Pickup, Barry T.; Thompson, Mark J.; Lomada, Santosh K.; Feng, Yuxi; Wieland, Thomas; Jackson, Richard F. W.; Muimo, Richmond (ChemBioChem, 2023)
Abstract Nonhydrolysable stable analogues of τ-phosphohistidine (τ-pHis) and π-pHis have been designed, aided by electrostatic surface potential calculations, and subsequently synthesized. The τ-pHis and π-pHis analogues (phosphopyrazole 8 and pyridyl amino amide 13, respectively) were used as haptens to generate pHis polyclonal antibodies. Both τ-pHis and π-pHis conjugates in the form of BSA-glutaraldehyde-τ-pHis and BSA-glutaraldehyde-π-pHis were synthesized and characterized by 31P NMR spectroscopy. Commercially available τ-pHis (SC56-2) and π-pHis (SC1-1; SC50-3) monoclonal antibodies were used to show that the BSA?G-τ-pHis and BSA?G-π-pHis conjugates could be used to assess the selectivity of pHis antibodies in a competitive ELISA. Subsequently, the selectivity of the pHis antibodies generated by using phosphopyrazole 8 and pyridyl amino amide 13 as haptens was assessed by competitive ELISA against His, pSer, pThr, pTyr, τ-pHis and π-pHis. Antibodies generated by using phosphopyrazole 8 as a hapten were found to be selective for τ-pHis, and antibodies generated by using pyridyl amino amide 13 were found to be selective for π-pHis. Both τ- and π-pHis antibodies were shown to be effective in immunological experiments, including ELISA, western blot, and immunofluorescence. The τ-pHis antibody was also shown to be useful in the immunoprecipitation of proteins containing pHis.
Online veröffentlicht: 14. Mai 2023
Gesehen am 16.10.2024